COMPARISON OF THE EFFICACY OF THREE IN VITRO MEDIA CULTURE FOR BLASTOCYSTIS SPP - Gallegos, Linda (2013)
Blastocystis is a chromist that can be found in the intestinal tract of animals and humans, and is currently considered an emerging pathogen with zoonotic potential. The aim of this study was to compare the efficacy of three in vitro media culture which are considered appropriate for the development of Blastocystis: Jones, Pavlova and Boeck-Drbohlav modified (BDM). It was used 54 stool samples from Blastocystis positive pigs diagnosed by the spontaneous sedimentation technique. The number of microorganisms inoculated was divided in three categories: low, intermediate and high. Each sample was cultivated for duplicate in the three media and after 72 hours of incubation the pathogens were counted using the Neubauer chamber. Results showed that the Jones media was the more efficient, followed by Pavlova and BDM; moreover, better results were obtained when the level of microorganisms was low. The cystic form was the most commonly observed in stool samples, whereas in culture media was the vacuolar followed by the granular form.